Corporate finance - Benninga, Simon (McGraw-Hill, 1997)
Designed for courses in corporate finance, this text is a detailed description of the valuation process, providing an integrated, comprehensive method for valuing assets, firms, and securities across a wide variety of industries. The presentation begins with a review of financial and accounting techniques, proceeds with a presentation of the valuation process, leading towards the development of pro-forma financial statements and the translation of these projections into values. A key strength of this text is teaching students how to use pro forma financial statements as a basis for valuation